Pelatihan Keuangan BUMDes : Sosialisasi Penyusunan Rencana Bisnis di Kecamatan Bontoa: Pelatihan Keuangan BUMDes : Sosialisasi Penyusunan Rencana Bisnis - Eldi Eldi; Andi Patiware; Yudi Achmad sadeli; Muh iksan (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2022)
BUMDes is one of the village business units that has the potential to be developed as an effort to move the economy in the village. Socialization of the preparation of business plans in BUMDes financial management training activities in the context of community service aims to improve skills and knowledge in preparing business plans. The activity was carried out in Bontoa District and the participants were BUMDes managers, totaling 29 people from 6 BUMDes. The method of delivering material is in the form of lectures, discussions and simulations. Activity results. The results of the activity show that socialization activities can increase the knowledge and motivation of BUMDes managers in improving skills in preparing business plans. This activity can be followed up in the form of training and technical guidance in the preparation of business plans.